MOTIVATION AND LINGUISTIC BARRIERS: WHY EFL LEARNERS STRUGGLE WITH SPEAKING SKILLS: MOTIVATION AND LINGUISTIC BARRIERS: WHY EFL LEARNERS STRUGGLE WITH SPEAKING SKILLS - Xakimbaeva, Zebiniso (Журнал иностранных языков и лингвистики, 2025)
In the modern world, English is not just a subject in school, but a global tool for communication, education, and success. However, despite many years of learning English, a large number of EFL (English as a Foreign Language) learners still struggle with speaking skills. This article aims to explore the major reasons behind this issue, with a focus on motivation, learning atmosphere, strict grammar rules, and psychological barriers.